French theater of social contestation at the turn of the 19th and 20th centuries: Women’s rebellion. (Louise Michel, Véra Starkoff, Nelly Roussel) - Kaczmarek, Tomasz (2022)
In the presented monograph, the author analyzes the dramas of the French theater of social protest, which was also created by women fighting for their civil rights. The anthology is devoted to three authors (Louise Michel, Véra Starkoff, Nelly Roussel) whose dramas have been translated into Polish for the first time. Until recently not many people recognized the feminist theater movement existing in the end of the 19th century. For almost a century it was condemned to oblivion for above all political reasons. Starkoff, the Russian Jew, was inspired by Tolstoy, Zola and Ibsen, and wrote the didactic dramas in which she discussed gender inequality between men and women at that time. She in her works seems to be more moderate then Russel who is more uncompromising in her works. Russell ridicules canonic values represented by the Roman-Catholic Church enslaving not only women but each individual’s thinking. And Michel describes an oppressive capitalist system that is based primarily on violence.
Keywords: Louise Michel; Véra Starkoff; Nelly Roussel; feminism; theater of protest